The Safety and Efficacy of Bacopa Monnieri (L) Wettst. in Older Adults with Subjective Cognitive Impairment: A Systematic Review - Pradeep, H.L.N.R.; Perera, P.K.; Waratenne, P.R.; Samaranayake, N.; Dissanayake, W.D.N. (University of Colombo, 2024)
This systematic review aims to evaluate the safety and efficacy of Bacopa monnieri in older adults with subjective cognitive impairment. A comprehensive search was conducted across major databases (PubMed, Google Scholar, Semantic Scholar, Library Databases: Research for Life and World Health Organization institutional repository) for randomized controlled trials and observational studies investigating Bacopa monnieri in older adults (aged 60 years and above) with subjective cognitive impairment or related conditions. Studies assessing cognitive function and safety parameters were included. Exclusion criteria for this review included reviews, case studies, editorials, conference proceedings, preclinical studies, trial protocols, book chapters, abstracts, and peer-reviewed articles in which the study population had a diagnosis of mild cognitive impairment or dementia. Data extraction and quality assessment were performed following PRISMA guidelines. Out of a total of 628 articles screened, 10 randomized controlled trial studies met the inclusion criteria. Results revealed that Bacopa monnieri supplementation demonstrated promising effects on cognitive function, particularly improvements in memory, attention, and executive function in older adults with subjective cognitive impairment. Safety analysis indicated that Bacopa monnieri is generally well-tolerated, with mild gastrointestinal discomfort being the most commonly reported adverse effect. Although long-term studies on its effects on anti-aging markers such as oxidative stress, inflammation, and cellular aging are limited, they suggest potential benefits. Bacopa monnieri shows potential as a safe and effective cognitive enhancer in older adults with subjective cognitive impairment. Preliminary evidence supports its use for improving cognitive function, with favorable safety outcomes. Future research should focus on larger, well-designed trials to confirm these findings.
Keywords: Bacopa Monnieri; Cognitive Function; Subjective Cognitive Impairment; Safety and Efficacy; Systematic Review